1998
DOI: 10.1159/000026157
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Acute Cortical and Subcortical Ischemic Stroke by Risk Factors and Clinical Examination Findings

Abstract: Background: Differentiation between acute cortical and subcortical ischemic stroke may be problematic when cortical stroke presents without obvious cortical deficits such as aphasia, neglect or hemianopia. This study explores stroke risk factors and clinical variables that may assist in this differentiation. Methods: Records of consecutive patients with acute ischemic stroke, examined within 72 h of symptom onset, were reviewed. Stroke type was verified by clinical course and follow-up imaging. Stroke risk fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…Cortical infarcts are usually the result of an embolus from the heart or large arteries (i.e., the aortic arch or carotid artery), whereas subcortical infarcts are caused by blockage of small penetrating arteries, and thus they are categorized as manifestations of cerebral small vessel diseases. 14 This is in line with the literature considering brain–kidney interactions to be based on small vessel disease in both organs. 15 In the present study we showed that larger decline in eGFR was associated with greater progression in white matter hyperintensity volume.…”
Section: Discussionsupporting
confidence: 87%
“…Cortical infarcts are usually the result of an embolus from the heart or large arteries (i.e., the aortic arch or carotid artery), whereas subcortical infarcts are caused by blockage of small penetrating arteries, and thus they are categorized as manifestations of cerebral small vessel diseases. 14 This is in line with the literature considering brain–kidney interactions to be based on small vessel disease in both organs. 15 In the present study we showed that larger decline in eGFR was associated with greater progression in white matter hyperintensity volume.…”
Section: Discussionsupporting
confidence: 87%
“…29,33 Among risk factors for stroke, age, hypertension, and diabetes mellitus were not found to be significantly different in cortical and subcortical stroke. 34 However, hypertension was shown to be strongly and independently correlated with silent cerebral infarctions. [35][36][37][38] Silent cerebral infarctions are frequently shown by CT and MRI in the subcortical white matter or the basal ganglia in patients who have had a stroke and in elderly subjects.…”
Section: Commentmentioning
confidence: 99%
“…In these studies, the size of the lesion in the brain was not related to functional outcome [ 2 , 3 ]. Few studies have reported on the relationships between brain lesions and functional recovery [ 5 7 ].…”
Section: Introductionmentioning
confidence: 99%